CLASSIFICAÇÃO PARA MADEIRA DE Pinus sp. LIVRE DE DEFEITOS A PARTIR DOS ANÉIS DE CRESCIMENTO - Breda, Augusto Melo Moulin (2022)
The Brazilian Standard (NBR) for Design of Wood Structures must consider for the mechanical classification and for the design of wood structures the association between physical-mechanical properties and the characteristics of the growth rings of Pinus sp. The characteristics of the growth rings are essential variables to estimate physical-mechanical properties of wood. Therefore, the objective of this dissertation is to evaluate the relationship between growth rings and physical-mechanical properties of clear specimens wood of Pinus sp. Non-destructive tests of longitudinal and transversal vibrations, stress wave, static bending, determination of basic and apparent densities, and destructive rupture test were performed. In addition, latewood width, latewood proportion, and number of growth rings were obtained. Pearson's correlation matrix was used to analyze the associations between physicalmechanical properties and growth rings characteristics’. Pearson’s r coefficients were all significant (p<0,05). Thus, it is concluded that the latewood width of the growth rings explained 62% of the basic density and 60% of the apparent density, but only 18% of the static bending. Therefore, the joint evaluation of growth rings characteristics and physical-mechanical properties enabled the mechanical characterization of Pinus sp. from growth rings.